ANTIMICROBIAL ACTIVITY OF THE LEAVES OF MYXOPYRUM SERRATULUM (International Journal of Pharmaceutical Sciences and Drug Research, 2012)
The antibacterial and antifungal activities of petroleum ether (40-60oC), benzene, chloroform, ethanol and water extracts of the leaves of Myxopyrum serratulum A. W. Hill. (Oleaceae) were tested for their antimicrobial activity in Agar diffusion assay. Significant antimicrobial activities were found against three gram positive bacteria, Streptococcus faecalis, Baccillus subtilis and Baccillus cereus, four gram negative bacteria; Klebsiella aerogens, Escherichia coli, Pseudomonas aeruginosa, Proteas vulgaris and two fungi, Candida albicans, Asparagillus flavans strains by using zone of inhibition assay. The activities were confirmed by Activity Index (AI). Activity Index values were found to be higher for ethanolic extract followed by the water extract. Among all the extracts tested; the ethanolic extract showed a good antimicrobial potential against microorganisms used in the study. The Minimum Inhibitory Concentration (MIC) for the ethanolic extract was also determined. The results support the ethnomedicinal use of Myxopyrum serratulum for the treatment of wounds and cuts.